Gender perspectives on mobile phone ownership and use: a case study of smallholder farmers in Uganda - Mulungu, Kelvin H. (Taylor and Francis, 2025)
Mobile phone-based Digital Agricultural Advisory Services (DAAS) offer cost-effective approaches for delivering agricultural extension to smallholder farmers, however, gender dynamics influence access and use patterns. Using focus group discussions with 49 women and 50 men farmers, complemented by key informant interviews with agricultural officers, we examined mobile phone ownership patterns and usage for agricultural purposes in rural Uganda. The findings reveal that while 94-98% of households own mobile phones, smartphone ownership remains limited (34%), with pronounced gender disparities. Both women and men use mobile phones to access information on agricultural inputs, markets, weather forecasts, and extension services through various platforms. However, there are institutional barriers, such as limited financial resources for devices and data bundles, poor network coverage, and restricted access to electricity. Gender norms further constrain women’s access, with lower digital literacy, inability to read in English, exacerbated lack of resources, time poverty, and reliance on men’s phones. To enhance inclusive access to digital agricultural services, we recommend integrating digital literacy programs targeting women, developing multilingual platforms, and adopting hybrid extension models that combine digital tools with face-to-face support. These interventions are essential to ensure equitable participation in Uganda’s digital agricultural transformation.